2008
DOI: 10.1007/s11431-008-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air annealing on the optical electrical and structural properties of In2S3 films

Abstract: The effect of the annealing temperature T a on the optical, electrical and structural properties of the In 2 S 3 films obtained by the spray pyrolysis method at 350 substrate temperature was studied. All the In 2 S 3 films annealed in the range from 100 to 400 are polycrystalline with (220) preferential orientation. The resistivity decreases as T a increases until it reaches a value of 25 Ohm-cm for T a =400 . The grain size also increases when T a increases as observed in data calculated from X-ray measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…These values position ALD-grown In 2 S 3 thin films as an interesting electronic material that compares well to In 2 S 3 thin films grown by other methods. 50,51 Like most polycrystalline films, these value fall short of bulk single crystal mobilities, which are reported to reach 200 cm 2 /(V•s). 52 A relatively constant carrier concentration is observed near ∼2 × 10 18 cm −3 at all growth temperatures.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These values position ALD-grown In 2 S 3 thin films as an interesting electronic material that compares well to In 2 S 3 thin films grown by other methods. 50,51 Like most polycrystalline films, these value fall short of bulk single crystal mobilities, which are reported to reach 200 cm 2 /(V•s). 52 A relatively constant carrier concentration is observed near ∼2 × 10 18 cm −3 at all growth temperatures.…”
Section: ■ Results and Discussionmentioning
confidence: 91%
“…This is an order of magnitude higher than that of films produced from the In­(acac) 3 ALD process (10 16 –10 17 cm –3 ), but significantly lower than carrier concentrations reported for In 2 S 3 films grown by some other methods. , For undoped In 2 S 3 films, the intrinsic donors are sulfur vacancies and indium interstitials. , These electronic properties suggest that growth with In­(amd) 3 forms more of these sites than growth with In­(acac) 3 , giving higher carrier concentrations. It is also likely in In­(acac) 3 grown films (given their large deficiency of S) , that these donor sites are reduced by oxygen incorporation in the films . The overall effect of growth temperature is an order of magnitude increase in conductivity that tracks the increasing mobility and charge carrier concentration with increasing growth temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, when b-In 2-x Al x S 3 samples annealed in air, the oxygen impurities are adsorbed on the surface of b-In 2-x Al x S 3 thin films. The presence of oxygen in the thin films could strongly modify the properties of the grain boundaries and this probably caused a decrease in electrical resistivity of the films [24]. For this reason, these thin films were annealed in air at 400°C on the hotplate, after their elaboration for different annealing times (15,30 and 45 min).…”
Section: Electrical Analysis Of Annealed B-in 2-x Al X S 3 (T = 646 Nmentioning
confidence: 99%
“…Many routes of preparation strategies had been applied for getting high-quality In 2 S 3 thin films, that were successfully synthesized using numerous techniques such as close space evaporation 11 , thermal evaporation 12 , 13 , chemical bath deposition 14 , 15 , physical vapor deposition 16 and spray pyrolysis 17 , 18 . It is found that the physical properties of the In 2 S 3 are strongly dependent on both the deposition technique and deposition conditions such as temperature and pressure, as well as annealing time 19 25 .…”
Section: Introductionmentioning
confidence: 99%